Expression of Myocilin Mutants Sensitizes Cells to Oxidative Stress-Induced Apoptosis : Implication for Glaucoma Pathogenesis - Joe, Myung Kuk (American Society for Investigative Pathology, 2010)
Mutations in the myocilin gene are associated with juvenile and adult-onset primary open-angle glaucoma. However, the pathogenic mechanisms of myocilin-induced glaucoma are still largely unknown. To investigate these mechanisms, we developed stably transfected HEK293 cell lines expressing wild-type or mutant (Y437H and I477N) myocilins under an inducible promoter. Expression of two mutant myocilins led to different levels of endoplasmic reticulum stress and increased apoptosis after treatment of cells with hydrogen peroxide. The Y437H mutant myocilin cell line showed the highest sensitivity to the oxidant treatment. Several antioxidant genes were down-regulated in the Y437H mutant myocilin cell line, but not in other cell lines. The Y437H mutant myocilin cell line also produced more reactive oxygen species than other cell lines examined. Consistent with the data obtained in cultured cells, the endoplasmic reticulum stress marker, 78 kDa glucose-regulated protein, was up-regulated, whereas antioxidant proteins, paraoxonase 2 and glutathione peroxidase 3, were down-regulated in the eye angle tissue of 18-month-old transgenic mice expressing Y437H myocilin mutant. In addition, a pro-apoptotic factor, CCAAT/enhancer-binding protein-homologous protein, was up-regulated in the aged transgenic mouse angle tissue. Our results suggest that expression of mutated myocilins may have a sensitization effect, which can lead to a severe phenotype in combination with oxidative stress. Mutant myocilins may confer different sensitivity to oxidative stress depending on the mutation.